The concept of wound healing algorithm - Jonathan Likoh Juis @ Juise; Teong, Khan Vun; Ryan MacDonnell Andrias; Jetol Bolongkikit; Siti Hasnah Tanalol; Asni Tahir (Pusat e-pembelajaran, UMS, 2023)
The purpose of this paper is to present a new optimisation algorithm based on nature-inspired wound healing process. Since optimisation problems have many local optimal solutions and non-linear patterns, there will be no global solution, reoptimisation could be a solution. We establish a wound healing algorithm as a better and more effective algorithm for multi-level optimization. The model is developed by taking essential process of wound healing to form the algorithm. Each major function involved in wound healing will be taken and defined according to the stage of the wound healing procedure. We emphasise the criteria of lightweight processing and reliability as the main expansions of the algorithm. Finally, we will analyse the model and algorithm in comparison with existing algorithms and provide insights on the performance and capabilities of the proposed models.